2015
DOI: 10.1007/978-3-319-26154-6_19
|View full text |Cite
|
Sign up to set email alerts
|

Qualifying Ontology-Based Visual Query Formulation

Abstract: Abstract. This paper elaborates on ontology-based end-user visual query formulation, particularly for users who otherwise cannot/do not desire to use formal textual query languages to retrieve data due to the lack of technical knowledge and skills. Then, it provides a set of quality attributes and features, primarily elicited via a series of industrial enduser workshops and user studies carried out in the course of an industrial EU project, to guide the design and development of successor visual query systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…OptiqueVQS is composed of communicating widgets (i.e., user-interface mashup) [48,13]. Along with flexibility, modularity, and adaptability, such an approach allow us combine multiple representation and interaction paradigms [49,47].…”
Section: Visual Query Formulationmentioning
confidence: 99%
“…OptiqueVQS is composed of communicating widgets (i.e., user-interface mashup) [48,13]. Along with flexibility, modularity, and adaptability, such an approach allow us combine multiple representation and interaction paradigms [49,47].…”
Section: Visual Query Formulationmentioning
confidence: 99%
“…Such an approach offers flexibility, modularity, and adaptability and enables us to combine multiple representation paradigms, such as forms, diagrams and icons, and interaction paradigms, such as schema navigation, range selection, and matching [12]. A multi-paradigm approach is important to support different user and task types as stated earlier [46,47].…”
Section: Optiquevqsmentioning
confidence: 99%
“…Since OptiqueVQS is a data retrieval (DR) tool, where a single missing or irrelevant object implies a total failure contrary to information retrieval (IR) [61,5], effectiveness is measured in terms of a binary measure of success (i.e., correct/incorrect query) and efficiency is measured in terms of total time taken to formulate a query [46,47]. The results of the experiment are presented in Table 4.…”
Section: User Studymentioning
confidence: 99%
See 1 more Smart Citation
“…(iii) Task synopsis: Domain experts' information needs are often structurally complex, requiring to join multiple relations. We have conducted a literature survey [85,86] to identify best practices and design patterns. The survey revealed that a multi-paradigm design combining multiple representation and interaction paradigms is key to address a broad range of user groups having frequent, unpredicted and sophisticated information needs [71,87].…”
Section: Visual Query Formulationmentioning
confidence: 99%